On the state of the organization of emergency medical care in Uzbekistan during the years of independence - Mukhlisa Soattullaevna Ergasheva (Genius Journals, 2022)
Protection of the population and the territory in emergencies, prevention of accidents, saving lives, correct response to emergencies, identification of specific aspects of health care, emergency medical care in emergencies to establish.
Keywords: Natural disasters; earthquakes; medical care; medical center